MAKING NATURE’S VALUE VISIBLE: VIDEO ARTISTS AS CITIZEN SCIENTISTS - Van Borek, Sarah (European Scientific Journal, ESJ, 2014)
Rewilding vancouver community projects was a community mapping, storytelling & visioning project designed to reconnect residents in the Metro Vancouver region of British Columbia, Canada with the city’s “wild side” (the historical natural environment) and to help “make visible” the different forms that nature takes in Vancouver as ways to inspire the valuing, protection and potential “rewilding” of nature.. The project was developed through a two-semester cross-disciplinary studio-based community projects course in the Faculty of Culture + Community at one of Canada’s leading post-secondary art institutions, the Emily Carr University of Art + Design (Vancouver), in partnership with one of Canada’s leading environmental organizations, the David Suzuki Foundation (DSF), and the bold, contemporary Museum of Vancouver (MOV). Postsecondary art students across a variety of levels and disciplines were facilitated in producing a media arts-based “virtual urban safari” as part of the MOV’s Rewilding Vancouver exhibit running February 27-September 1, 2014. This exhibit is believed to be the first of its kind in Canada to feature the historical ecology of a major city. Many of the students, by their own self-description, came into the course feeling disconnected from the natural world themselves. The course was structured in a way that encouraged students to reconnect with nature in the city through their creative process. The course culminated in a public screening and dialogue, offering the students the opportunity to see the effects of their work on a public audience and feel like their input could have an impact.